2000
DOI: 10.1016/s0378-1097(99)00587-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux in glucose/citrate co-fermentation by lactic acid bacteria as measured by isotopic ratio analysis

Abstract: The flux of carbon into lactic acid, diacetyl and acetoin during the co-metabolism of glucose and citrate by Lactococcus lactis subsp. lactis biovar. diacetylactis has been determined using natural abundance isotopic ratio analysis. During fermentation in the conditions used (glucose, 27.8 mM; citric acid, 13.9 mM; initial pH 6.2^6.4, anaerobic) it is shown that approximately 65% of the carbon source used for the aroma compounds is derived from the carbohydrate. Equally, citrate contributes approximately 30% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…The co-metabolism of glucose and citrate by Lactococcus lactis subsp. lactis biovar diacetylactis indicated that 65% of the carbon source was converted to flavour producing compound (Goupry et al, 2000). The co-metabolism of xylose and citrate gave high yields of diacetyl and acetoin, 11.5% in batch culture and 17.4% in chemostat culture by Leuconostoc mesenteroides subsp.…”
Section: Introductionmentioning
confidence: 99%
“…The co-metabolism of glucose and citrate by Lactococcus lactis subsp. lactis biovar diacetylactis indicated that 65% of the carbon source was converted to flavour producing compound (Goupry et al, 2000). The co-metabolism of xylose and citrate gave high yields of diacetyl and acetoin, 11.5% in batch culture and 17.4% in chemostat culture by Leuconostoc mesenteroides subsp.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolism of citric acid has been extensively studied and it is well documented in species of Lactobacillus ( L. casei , Lactobacillus plantarum , and Lactobacillus rhamnosus ; Goupry and others ; Vaningelgem and others ). According to Williams and others (), Lactobacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…These strains are unusual in their capacity to accumulate the C4 products, diacetyl, acetoin and butan‐2,3‐diol. This correlation led to a number of reports that these compounds were products of citrate catabolism [7–9] but recent work has disproved this assumption [10,11]. Although the metabolism of citrate to pyruvate does not consume NAD + , acetoin and butan‐2,3‐diol production can contribute to NAD + regeneration.…”
mentioning
confidence: 99%
“…What is apparent is that the cometabolism of citrate and glucose leads to the enhanced production of these compounds by re‐routeing of the metabolic throughput [3,7–9,16,17]. Because this is not specifically due to the metabolism of citrate to the C4 compounds [10,11], it must reflect an overall shift in the balance between different routes for pyruvate catabolism. This shift could be a response to an altered redox status or simply an up‐shift in the size of the pyruvate supply.…”
mentioning
confidence: 99%
See 1 more Smart Citation